Relationship between Trade Liberalisation, Growth and Balance of Payments in Developing Countries: An Econometric Study - Ashok Parikh (Hamburg Institute of International Economics (HWWA), 2004)
The objectives of this paper are to study the impact of liberalisation on trade deficits and current accounts of developing countries. It is expected that trade liberalisation would promote economic growth from the supply side by leading to a more efficient use of resources, by encouraging competition, and by increasing the flow of ideas and knowledge across national boundaries. Trade liberalisation could lead to faster import growth than export growth and hence the supply side benefits may be offset by the unsustainable balance of payments position. This study uses panel data of 42 countries (both time-series and cross-section dimension) to estimate the effect of trade liberalisation and growth on trade balance while controlling for other factors such as income terms of trade. The major finding of the study is that trade liberalisation promotes growth in most cases, (Part 1 of this study) the growth itself has a negative impact on trade balance and this in turn could have negative impacts on growth through deterioration in trade balance and adverse terms of trade. Our conclusion is that trade liberalisation could constrain growth through adverse impact on balance of payments.
Keywords: F32; C21; F13; C23; C22; F14; 330; Panel data; Income Terms of Trade; Dynamic Optimisation; Dynamic panel model; Aussenhandelsliberalisierung; Wirtschaftswachstum; Handelsbilanz; Zahlungsbilanzungleichgewicht; Schätzung; Terms of Trade; Dynamische Optimierung; Entwicklungsländer